Demand Side Energy Management for Linear Programming Method - N. Loganathan; K. Lakshmi (Institute of Advanced Engineering and Science, 2015)
This paper presents an optimization method to the Demand Side Energy Management System (DSEMS) of a given consumer (e.g.an industrial compound or university campus) with respect to hourly electricity prices. The demands can be supplied through the main grid and stochastic Distributed Energy Resources (DERs), such as wind and solar power sources. To solve this DSEMS problem and optimization algorithm based on Linear Programming (LP) approach has been implemented. The objective of the proposed method is to maximize the utilization of the cluster of demands. This LP algorithm allows the cluster of demand to buy, store and sell energy at suitable times to adjust the hourly load level. To evaluate the performance of the proposed algorithm an IEEE 14 bus system was considered. The results shows that the cluster of demands of energy management system using the proposed approach increasing the efficiency and minimizing the losses than the existing methods. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7570